Controle do cupim de montículo (Isoptera: Termitidae) de pastagem com fungos entomopatogênicos - Toscano, Luciana Claudia; Schlick-Souza, Eunice Cláudia [UNESP]; Martins, Gustavo Luís Mamoré; Souza-Schlick, Genivaldo David [UNESP]; Maruyama, Wilson Itamar (My University, 2010)
The objective of this study was to evaluate the control of mound-building termites (Isoptera: Termitidae) by entomopathogenic fungi (Metarhizium anisopliae and Beauveria bassiana). We developed two experiments, with two copies of application in three sizes of nests. The first was installed in the Salto Macaúba farm and second in the Laboratory of Plant Protection at the State University of Mato Grosso do Sul. The first experiment consisted of five repetitions, each nest an experimental unit, with treatments in a factorial 2 (fungi) × 2 (tests) × 2 (type of spraying) + 1 control, distributed completely at random in the area. The treatments were: 1) control - no implementation, 2) Metarril M103 (M. anisopliae) - 10g/mound - dusting, 3) Metarril M103 - 10 g/ mound - via net, 4) Metarril M103 - 15 g/ mound - dusting, 5) Metarril M103 - 15 g/mound - via net, 6) Boveril B102 (B. bassiana) - 10 g/mound - dusting, 7) Boveril B102 - 10 g/mound - via net, 8) Boveril B102 - 15 g/mound - dusting and 9) Boveril B102 - 15 g/mound - via net. The testing of mortality were made spraying of the laboratory with the field measurements performed in compliance with the same separation of the nests. The results suggested that the road dust (dosage of 10 g) of the fungi studied showed higher mortality of nests of small size (53%). B. bassiana (Boveril) (10 g) gave 80% mortality of C. cumulans when applied to nests of small size.
Control of mound-building termite (Isoptera: Termitidae) of pasture with entomopathogenic fungus
Keywords: Beauveria bassiana; Biological control; Cornitermes cumulans; Metarhizium anisopliae